PECULIARITIES OF THE SOVIET UNDERGROUND AND PARTISAN MOVEMENT IN “GALICIA” DISTRICT (1941 – 1944) - SHCHEHLOV, Andrii (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to determine the ethnic composition of the Soviet self-organized underground organizations and partisan detachments in “Galicia” district during the Nazi occupation and to clarify the participation of the Polish population in the underground organizations and partisan detachments. The research methodology is based on the principles of systematicity, scientificity, historicism and comprehensiveness. In the research, historical comparative, problem-chronological, retrospective methods, and the method of criticism of historical sources have been used. The scientific novelty consists in the fact that for the first time the author, based on a critical analysis of the Ukrainian historiography and information sources, has determined the role of the “Polish” factor in the formation and activity of underground and partisan organizations and groups in the region. In the conclusions, the author proceeds from the fact that the Soviet underground and partisan movement in the district “Galicia” was small and relatively weak. It is also quite debatable to apply to it such definitions as “partisan” or “resistance movement”. The reason for this is the lack of a critical mass of the local population in its ranks and a clear organization of efforts to resist the Nazi occupation authorities. The predominantly Ukrainian population of the region did not support such a movement. Considering the above mentioned facts of the archival sources analysis and the results of previous research, we should determine a significant role of the “Polish” influence on the organization and activities of the Soviet underground and partisan cells in the district. This significant role was manifested both in the active participation of the Polish anti-Hitler underground of the pro-Soviet leftist orientation, and the local Polish ethnic population, which, not always willingly, but under the power of circumstances, began its cooperation with non-local organizers of local groups of underground partisan struggle – the Soviet soldiers and communists. An additional factor in such cooperation was the peak of the Ukrainian-Polish conflict in Western Ukrainian lands during World War II. In every way the Soviet and pro-Soviet historiography tried to conceal the fact of a significant Polish influence on the above mentioned forms of struggle. The aim of such activity was to support the myth of “people’s Soviet avengers”, “nationwide struggle against fascism under the Soviet power leadership”, etc. Key words: district “Galicia”, the Poles, the Soviet partisans, the Soviet underground, occupation.